Generating advanced CAR-based therapy for hematological malignancies in clinical practice: targets to cell sources to combinational strategies - Zhou, Shu; Yang, Yuhang; Jing, Yulu; Zhu, Xiaoying (Frontiers in Immunology, 2024)
Chimeric antigen receptor T (CAR-T) cell therapy has been a milestone breakthrough in the treatment of hematological malignancies, offering an effective therapeutic option for multi-line therapy-refractory patients. So far, abundant CAR-T products have been approved by the United States Food and Drug Administration or China National Medical Products Administration to treat relapsed or refractory hematological malignancies and exhibited unprecedented clinical efficiency. However, there were still several significant unmet need to be progressed, such as the life-threatening toxicities, the high cost, the labor-intensive manufacturing process and the poor long-term therapeutic efficacy. According to the demands, many researches, relating to notable technical progress and the replenishment of alternative targets or cells, have been performed with promising results. In this review, we will summarize the current research progress in CAR-T eras from the "targets" to "alternative cells", to "combinational drugs" in preclinical studies and clinical trials.